A scoping review of personalisation in the UK: approaches to social work and people with learning disabilities. (6th May 2013) - Sims, David; Cabrita Gulyurtlu, Sandra S.
Abstract There have been rapid developments in personalisation of health and social care in the UK over the past 5 years to develop a more flexible model of provision based upon greater choice and control for service users. This has been important for people with learning disabilities who are often dependent on others such as social workers to support their autonomy and independence. This article discusses a study carried out to explore the impact of personalisation on people with learning disabilities and the role of social workers to support this. A scoping review of the UK literature from 1996 to 2011 was conducted. It was found that there has not been a significant amount of empirical research in this area. Some studies, such as reports by InControl, have suggested that when implemented well, personalisation can have a positive impact on the lives of people with learning disabilities. Other literature highlighted the limitations and critiques of personalisation. Without the right support to manage budgets and autonomy, people with learning disabilities could be left vulnerable. In respect of the social workers, the finding of the review was that there was a lack of guidance on how to implement personalisation and a perceived threat to their traditional practice role, resulting in barriers to implementation. Although the literature emphasises the need for choice, control and autonomy in personalisation, the conclusion of this study is that more research needs to be carried out into how professional roles fit into and can support this process.